Fish and fish-liver oil consumption in adolescence and midlife and risk of CHD in older women. Issue 2 (17th April 2015) - Haraldsdottir, Alfheidur; Torfadottir, Johanna E; Valdimarsdottir, Unnur A; Aspelund, Thor; Harris, Tamara B; Launer, Lenore J; Gudnason, Vilmundur; Steingrimsdottir, Laufey
Abstract: Objective: To study the association of fish and fish-liver oil consumption across the lifespan with CHD later in life among Icelandic women, with special emphasis on the effects of consumption in adolescence. Design: Prevalence association study. Logistic regression was used to estimate odds ratios and 95 % confidence intervals of CHD according to fish or fish-liver oil exposure. Models were adjusted for age, education, concurrent diet and other known risk factors. Setting: The study was nested within the AGES-Reykjavik Study, conducted in Reykjavik, Iceland. Subjects: Participants were 3326 women aged 66–96 years, with available information on CHD status at entry to the study and information on fish and fish-liver oil consumption during midlife and adolescence. Dietary habits were assessed retrospectively using a validated FFQ. Results: CHD was identified in 234 (7·9 %) women. Compared with women with no intake of fish-liver oil in adolescence or midlife, women who consumed fish-liver oil at least three times weekly in adolescence or in midlife had a decreased risk of CHD (OR=0·62; 95 % CI 0·45, 0·85 and OR=0·68; 95 % CI 0·50, 0·94, respectively). No associations were observed between fish intake (>2 portions/week v . ≤2 portions/week) in adolescence or midlife and CHD in this population with high fish intake. Conclusions: Fish-liver oil consumption, from early life, may reduce the risk of CHD in older women. Lifelong nutrition may be of importance in the prevention of CHD in older women.